2018
DOI: 10.1002/cl2.202
|View full text |Cite
|
Sign up to set email alerts
|

PROTOCOL: Counter‐narratives for the prevention of violent radicalisation: A systematic review of targeted interventions

Abstract: Galway, under the supervision of Dr Kiran Sarma. Sarah Carthy will coordinate and conduct the review. Colm Doody will act as second coder for the study selection process. Dr O'Hora and Dr Sarma will supervise the review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…No specific intervention toward aggressors was found, and most projects focused on prevention or on victims, through confidence and skills building such as learning to speak out, report, and potentially react in an appropriate way. We support the recommendations offered by Carthy et al (2018) and Blaya (2019) that additional research is needed in this area to properly interpret the effectiveness of online interventions aimed at reducing online hate speech and cyberhate.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…No specific intervention toward aggressors was found, and most projects focused on prevention or on victims, through confidence and skills building such as learning to speak out, report, and potentially react in an appropriate way. We support the recommendations offered by Carthy et al (2018) and Blaya (2019) that additional research is needed in this area to properly interpret the effectiveness of online interventions aimed at reducing online hate speech and cyberhate.…”
Section: Discussionsupporting
confidence: 82%
“…Two reviews offer additional insight into the current state of online hate speech and cyberhate interventions. First, Carthy et al (2018) assessed the effectiveness of counter‐narratives in reducing the risk of violent radicalization. While the authors found little evidence that counter‐narratives are effective at targeting the intent to act violently, they concluded that these counter‐narrative interventions might affect some risk factors (e.g., realistic threat, in‐group favoritism, out‐group hostility) related to violent radicalization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations